Mitochondrial Ferritin in Erythroid Cells from patients with Myelodysplastic Syndrome - Zulfiqar Ali, Afsheen Akbar, Nida, Sidra Tul Huda, Faiza Habib, Aamna Habib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The Myelodysplastic syndrome (MDS) is extremely fatal illness whither anaemia is insensitive to any medical management. Aim: In present research, effect of levels of ferritin in serum lying on prospects and continued existence was scrutinize in MDS subjects with no previous record of blood transfuse. Study design: Retrospective. Methods: These cases (MDS) were alienated into two groups, according to their serum ferritin levels. Sample size of 58 cases of MDS calculated according to online service “Select Statistical Services Ltd” comparing two means. Results: The time of endurance mean was 5.09 years ± 4.8 months. Median ferritin levels of serum ferritin were 358 ng /ml. The plasma ferritin level is related with higher rate of mortality with levels as 500 ng/ml. The ROC part for Serum ferritin was 0.721 by means of a cut-off range of 401; susceptibility and explicitness. were 71.7% and 69.1%, correspondingly) P=0.002. In attendance were 33 subjects with value of ferritin is ≥ 500 ng/ml. Patients with serum ferritin values ≥ 500 ng/mL had lower survival expectancy. Ferritin ≥ 500 ng/mL be related with seven folds augmented death rates (P = 0.001). Practical Implication: In MDS iron chelation is not well-known, for that reason the overall survival is not good. The iron chelation might encompass a favorable outcome on survival of MDS. Conclusion: Even though 1000ng/ml ferritin value in the beginning of chelation therapy is adequate, reduced survival expectancy will be associated with high levels of serum ferritin. Keywords: Myelodysplastic syndrome, ferritin, chelation, ring sideroblast, isoniazid, penicillamine